Comparison of cardiovascular risk factors and dietary intakes among Javanese Surinamese and South-Asian Surinamese in the Netherlands. The HELIUS study - Raza, Qaisar (BMC Res Notes, 2017)
BACKGROUND: Ethnic differences regarding the percent of non-communicable diseases have been shown in Asia but the studies on Asian subgroups living in the western countries regarding percent of cardiovascular risk factors and dietary intakes have been scarce. Therefore we compared the percent of cardiovascular risk factors and dietary intakes between Javanese Surinamese who are originally from Indonesia and South-Asian Surinamese who are originally from India. METHODS: Cross-sectional baseline data of the HELIUS (Healthy Life in an Urban Setting) study were used, including data of 2935 Surinamese participants (197 of Javanese and 2738 of South-Asian origin) out of which 1160 participants (78 Javanese and 1082 South-Asian) additionally reported dietary intake data. Descriptive statistics were used to compare the two ethnic groups regarding cardiovascular disease, diabetes, obesity, hypertension and hypercholesterolemia; in addition, dietary intake of foods like vegetables, red meat, fruit, high fibre foods, low fibre foods, high fat and low fat dairy products, chicken and sugar sweetened beverages were also compared between the two groups. Binary logistic regression analyses were used to adjust for age and sex when comparing the two groups. RESULTS: South-Asian Surinamese had a significantly higher percent of abdominal obesity (OR 2.44; CI 1.66–3.57), cardiovascular disease (OR 2.55; CI 1.48–4.35) and diabetes (OR 2.77; CI 1.67–4.60) as compared with Javanese Surinamese after adjustment for age and sex. The percent of obesity (BMI), hypertension, and lipids was not significantly different between the ethnic groups. Javanese Surinamese had a significantly higher intake of red meat and a significantly lower intake of dairy products as compared with South-Asian Surinamese. Intakes of vegetables, grains, fish, fruits, tea and coffee did not significantly differ between the ethnic groups. Both groups showed intake of considerable amount of sugar sweetened beverages. CONCLUSIONS: Public health practitioners in the Netherlands and elsewhere in the world should take into account the ethnic subgroup differences within the broader groups like Asians when developing interventions related to health among ethnic minorities.